SISTEM INFORMASI PENJUALAN SUPPLIER BERBASIS ANDROID - CHANG, FELIX; Amrizal (Computer Science and Industrial Engineering, 2022)
In this digital era, information systems are very important for all parties, especially for supplier businesses. Information systems have been applied to many companies ranging from small companies to large companies, so it can be said that information systems have become a basic need for people doing business. Information system is needed to help the work processes more efficiently because of its advantages that it can store information, process, and send information anytime and from anywhere as long as we hold a smartphone device that we always carry everywhere every day. Especially for supplier businesses that will deal with stock recording activities, orders from customers, and sales reports, therefore this study designed an Android-based system application to help so that stock recording is not done manually using handwriting, customer order data can be stored properly, and making sales reports automatically. The software used in building this application are visual studio, xampp, android studio. With the development of this android-based information system, it is hoped that it can help improve and expand the business performance by meeting the needs described above.